Odynophagia: A Rare Presenting Symptom in Acute Myeloid Leukemia (FAB AML - M2) - Yadav, Sudip; Kafle, Neeta; Sapkota, Sulav (Birat Journal of Health Sciences, 2021)
Acute myeloid leukemia is more common in adults than in children population. Fatigue, bleeding and fever are the most common presentations. Petechiae, gingival swelling, lymphadenopathy and hepatosplenomegaly are common signs. Here we report a case of a 57 years post-menopausal lady with gum swelling and pain on deglutition for both liquid and solid foods. She was diagnosed with a case of AML- M2 on the basis of peripheral blood smear and bone marrow examination findings.